Pengaruh Budaya Organisasi, Kepuasan Kerja dan Komitmen Kerja terhadap Kinerja Karyawan pada Koperasi PRIMKOPPOL Polres Palangka Raya - Sri Damayanti; Saladin Ghalib; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2017)
The purpose of this study is to determine the effect of 1). The organization practice (X1), on the satisfication of work performance (X3), the organizational performance (X3), the organizational commitment (X3), and the employees’ work performance (Y), 2). The satisfication of work performance (X2) on the organizational commitment (X3) on the employees’ work performance (X).The population of this study are all of the employees at the cooperation of Primkoppol Polres Palangkaraya as much as 26 and all of them were taken as the sample of this study. For data collection, researcher used questionnaire which was designed by the Likert scale level 1-5. The data analysis used is SmartP1.5 structural model.The result of the study proved, 1). The organizational practice (X), influential significantly on the work performance satisfication (X2), the organizational commitment (X3) and the employees’ work performance, the quality of the effect respectively are 70,55%, 59,69% and 82,14%. The satisfication of work performance (X2) influential significantly on the organizational commitment (X3) and employees’ work performance (Y) with the effect quantity for each are 47,31% and 38,16%. The organizational commitment (X3) influentially not significant on the employees’ work performance (Y) with the effect quantity (-14,13%). Keywords: the organizational practice, work performance satisfication, the organizational commitment, and employees’ work performance.